A Systematic Review of the Impact of Dedicated Emergency Surgical Services on Patient Outcomes. Issue 1 (January 2016) - Chana, Prem; Burns, Elaine M.; Arora, Sonal; Darzi, Ara W.; Faiz, Omar D.
Abstract : Objective: This review aims to assess the impact of implementing dedicated emergency surgical services, in particular acute care surgery, on clinical outcomes. Background: The optimal model for delivering high-quality emergency surgical care remains unknown. Acute Care Surgery (ACS) is a health care model combining emergency general surgery, trauma, and critical care. It has been adopted across the United States in the management of surgical emergencies. Method: A systematic review was performed after PRISMA recommendations using the MEDLINE, Embase, and Psych-Info databases. Studies assessing different care models and institutional factors affecting the delivery of emergency general surgery were included. Results: Twenty-seven studies comprising 744, 238 patients were included in this review. In studies comparing ACS with traditional practice, mortality and morbidity were improved. Moreover, time to senior review, delays to operating theater, and financial expenditure were often reduced. The elements of ACS models varied but included senior clinicians present onsite during office hours and dedicated to emergency care while on-call. Referrals were made to specialist centers with primary surgical assessments taking place on surgical admissions units rather than in the emergency department. Twenty-four-hour access to dedicated emergency operating rooms was also described. Conclusions: ACS models as well as centralized units and hospitals with dedicated emergency operating rooms, access to radiology and intensive care facilities (ITU) are all factors associated with improved clinical and financial outcomes in the delivery of emergency general surgery. There is, however, no consensus on the elements that constitute an ideal ACS model and how it can be implemented into current surgical practice.